Formation of the Economic Potential of the Enterprise (Service Enterprises – Repair and Maintenance of Vehicles) Evidence from Bosch Company - Azhaman, Iryna A.; Zhydkov, Oleksiy I.; Hronska, Maryna V.; Petryshchenko, Nataliia A.; Serohina, Nataliia V. (International Journal of Criminology and Sociology, 2021)
The study discusses the formation of the economic potential of an enterprise (Bosch company), as exemplified by service enterprises involved in the repair and maintenance of vehicles. The relevance of research in this area is determined by the large number of operating Bosch service companies engaged in servicing vehicles and the breadth of their services, which largely determines the firm's policy and forms its economic potential. The identification of criteria for assessing the formation of the economic potential of the enterprise, it is important to determine the economic patterns of development of enterprises operating in automobile service, contributes to a better understanding of the patterns that affect the development of enterprises in the automotive sector at large. Furthermore, the economic potential of the enterprise is formed as a joint result of its economic and business activities, and the presence of an extensive network of Bosch service enterprises significantly expands the possibilities for conducting such activities. Thus, there is a direct correlation between the number of Bosch automobile service enterprises, the services rendered by them in repair and maintenance of motor vehicles, the quality of work of such service enterprises and the formation of the economic potential of Bosch at large. The results of this study can be of significant practical importance for functioning and newly created enterprises in automobile transport service maintenance, in the aspect of identifying and stating fundamental principles that influence the formation of their economic potential and improve the quality of their work in general.